Statistical-model calculations for α-capture reactions relevant to the p process - Fakiola, C.; Karakasis, I.; Sideris, I.; Khaliel, A.; Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2019)
About 35 nuclides which lie on the neutron deficient side of the isotopic chart cannot be created by the two basic nucleosynthetic processes, the sand the rprocess. Due to scarce experimental data and the vast complexity of the reaction network involved, cross sections and reactions are estimated theoretically, using the Hauser–Feshbach statistical model. In the present work, theoretical calculations of cross sections of radiative α-capture reactions on the neutron–deficient Erbium and Xenon isotopes are presented in an attempt to make predictions inside the astrophysically relevant energy window (Gamow). The particular reactions are predicted to be sensitive branchings in the γprocess path. The most recent versions of TALYS (v1.9) and Fresco codes were employed for all calculations, initially focusing on investigating the influence of the default eight (8) α–nucleus optical potential models of TALYS on reaction cross sections. The theoretical results of both codes are compared and for the reactions where experimental data exist in literature, the optical model parameters were adjusted appropriately to best describe the data and were subsequently used for estimating (α,γ) reaction cross sections. Predictions for the (α,n) reaction channels have also been calculated and studied.